Divergent Characteristics of T-Cell Receptor Repertoire Between Essential Hypertension and Aldosterone-Producing Adenoma - Chang, Che-Mai; Peng, Kang-Yung; Chan, Chieh-Kai; Lin, Yu-Feng; Liao, Hung-Wei; Chang, Jan-Gowth; Wu, Mai-Szu; Wu, Vin-Cent; Chang, Wei-Chiao (Frontiers in Immunology, 2022)
Aldosterone-producing adenoma (APA) is a benign adrenal tumor that results in persistent hyperaldosteronism. As one major subtype of primary aldosteronism, APA leads to secondary hypertension that associated with immune dysregulation. However, how adaptive immune system, particularly the T-cell population, is altered in APA patients remains largely unknown. Here, we performed TCR sequencing to characterize TCR repertoire between two age-matched groups of patients: one with APA and the other one with essential hypertension (EH). Strikingly, we found a significant reduction of TCR repertoire diversity in the APA group. Analyses on TCR clustering and antigen annotation further showed that the APA group possessed lower diversity in TCR clonotypes with non-common antigen-specific features, compared with the EH group. In addition, our results indicated that the strength of correlation between generation probabilities and frequencies of TCR clonotypes was significantly higher in the APA group than that in EH group. Finally, we observed that clinical features, including plasma aldosterone level, aldosterone-renin ratio and blood sodium level, were positively associated with the strength of correlation between generation and abundance of TCR clonotypes in the APA group. Our findings unveiled the correlation between T-cell immune repertoire and APA, suggesting a critical role of such adrenal adenoma in T-cell immunity of hypertension patients.